Seasonal abundance and diversity of spiders (Arachnida: Araneae) in rice ecosystem of Himachal Pradesh - Chhavi, Ms.; Sharma, Pawan K; Dhali, Dhruba Chandra (ORYZA-An International Journal of Rice, 2021)
Spiders are one of the most fascinating and diverse invertebrates and also potential bio-control agents in agroecosystems. Field surveys were carried out at Sundernagar, Jogindernagar, Nurpur and Palampur areas of Himachal Pradesh by two methods namely visual count and sweep net to assess seasonal abundance and diversity of spider, in the rice ecosystems during kharif, 2015 and 2016. It was found that the population trend was well represented by visual count method as compared to sweep net method. Maximum numbers of spiders were recorded from Palampur area followed by Sundernagar, Jogindernagar and Nurpur. Eleven families viz., Oxyopidae, Tetragnathidae, Salticidae, Lycosidae, Pisauridae, Araneidae, Theridiidae, Clubionidae, Sparassidae, Thomisidae and Pholcidae were recorded from the fields with majority belonging to Araneidae and Tetragnathidae. The pre-dominant spider genus from all the locations were Tetragnatha and Neoscona while Araneus pseudosturmii and Runcinia ghorpadei Tikader were confined only to Nurpur and Sundernagar, respectively. A. pseudosturmii and Micropholcus fauroti Simon seem to be the first records from India while R. ghorpadei to be the hitherto unknown male morph.